A Review of Techniques Used to Suppress Tremor - Shelan Khudhur Saleh; Saleem Lateef Mohammed; Ali Al-Askery (Journal of Techniques)
The most frequent movement disorder is Tremor, which has an increased incidence and prevalence in people over 65 who have Parkinson's disease or essential tremors. Although not life-threatening, it prevents patients from performing their daily activities. An overview of different types of tremors and their treatment in medical and surgical views are discussed in this paper with a review of the stimulation nerves and muscles technique. Then a look at tremor detection and measurement methods are considered with a review of the medical devices' mechanism of action that is placed as a substitute treatment for patients that have a low response to medications and surgical treatment to provide effective and safe tremor suppression.